1995
DOI: 10.1016/0370-2693(94)01378-p
|View full text |Cite
|
Sign up to set email alerts
|

Braaten-Pisarski method at finite chemical potential

Abstract: The effective perturbation theory developed by Braaten and Pisarski for gauge theories at finite temperature is extended to finite chemical potential.As a first application the collisional energy loss of a heavy quark propagating through a quark-gluon plasma with non-vanishing quark chemical potential is considered. Assuming µ/T ≃ 1, motivated by numerical simulations of heavy ion collisions at RHIC energies, we find that the effect of the quark chemical potential is rather small, unless the energy density ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 33 publications
4
80
0
Order By: Relevance
“…In hard-thermal-loop (HTL) approaches [54,55] the damping of a hard quark (or gluon) does not depend on the quark chemical potential explicitly [57] and one might employ (6) also at finite µ. This, however, has to be considered with care since HTL approaches assume small couplings g 2 and should be applied at sufficiently high temperature, only.…”
Section: Finite Quark Chemical Potential µ Qmentioning
confidence: 99%
“…In hard-thermal-loop (HTL) approaches [54,55] the damping of a hard quark (or gluon) does not depend on the quark chemical potential explicitly [57] and one might employ (6) also at finite µ. This, however, has to be considered with care since HTL approaches assume small couplings g 2 and should be applied at sufficiently high temperature, only.…”
Section: Finite Quark Chemical Potential µ Qmentioning
confidence: 99%
“…Actually, HTLs were also studied when a chemical potential was included for quarks, and it was concluded that the only effect of the chemical potential was modifying the Debye mass by a term proportional to the chemical potential [17], [18]. Therefore, at very high density or chemical potential µ and zero temperature, one also may expect that naive one-loop computations are incomplete, as one-loop diagrams with soft (∼ gµ) external momenta, and quarks running inside the loop with Fermi energy, are comparable to tree amplitudes, and therefore they would have to be resummed.…”
mentioning
confidence: 99%
“…In the case of a weak external field, the screening of the one-gluon interaction in dense medium can be described well by the usual hard-dense loop approximation [34][35][36]. In the Coulomb gauge, the Lorentz structure of the gluon propagator is given by [37,38] …”
Section: A Gluon Propagatormentioning
confidence: 99%
“…In the most important regime for Cooper pairing dynamics, q 0 ≪ | q| ≪ m D , the approximate expressions for these screening functions read [34][35][36] …”
Section: A Gluon Propagatormentioning
confidence: 99%